Liver radioembolization with 90Y microspheres - Reiser, Maximilian F.; Bilbao, Jose Ignacio (Medical Radiology, 2014)
This is the second edition of a very well received book devoted specifically to the treatment of liver tumors by radioembolization with 90Y microspheres. The success of the first edition was based on the provision of all the fundamental information required for successful use of this therapeutic modality in clinical practice. The new edition has been fully updated to cover the most recent advances and includes additional chapters on regulations and emerging trends. Detailed information is provided on the full range of relevant topics, including hepatic vascular anatomy (including variants), dosimetry, assessment of tumor response, and the results achieved using radioembolization alone and in combination with other treatments in patients with primary or metastatic disease. Complications and side-effects are also fully discussed. This book will prove immensely valuable for both beginners and practitioners.